Implantação da Política Nacional da Atenção Integrada à Saúde do Homem: análise das possibilidades e limites. - Chianca, Kirlene Scheyla Viana (2011)
The present work has as scope to assess, from the nurses USF Integrated teams, what are the possibilities and limitations for the deployment of PNAISH the city of João Pessoa - PB. The purpose of this evaluation, accordingly, is to reduce the uncertainties in the decision-making in health, revealing to society the consequences and effects of the deployment and implementation of this policy, especially in primary care. The inclusion of different population groups in primary health has not been equitably. An example can be represented by a shortage of health related to man, given that this long not received necessary attention, which resulted in a framework of morbidity and mortality of concern. It can be stated that the situation of human health presents a challenging profile in relation to public policies, because their problem solving means, among other things, to broaden the discussion about the harsh conditions and chronic health of this population group and implement specific actions, based on this context, we developed the thesis in question. In line with the objectives, if this is an exploratory study with qualitative and quantitative approaches. The study environment comprised the USF picked Integrated João Pessoa - PB corresponding to the junction of four basic health units that support each other to meet the demands of population health. To address the problematic issue that guided the study were interviewed 12 nurses who deliver on those activities Integrated USF. The data were processed using quantitative and qualitative elements in order to meet the objectives proposed in the research. It can be seen through analysis and discussion of results that the specific actions to human health are almost nonexistent in the USF, as this audience is not receptive, men being quite resistant to the actions of health, and it does not exist a consistent policy, geared specifically for this audience. It appears from building on the interviewees' reports that the key issue would contribute to the implementation of PNAISH is the training of professional staff, as to respondents, the space to develop the action is, therefore, the deficiency is found the lack of capacity to support programs for human health.